'Not dead but sleeping': Expanding international law to better regulate the diverse effects of ceasefire agreements. (September 2020) - Sosnowski, Marika
Abstract: Ceasefire agreements are legally governed by international humanitarian law because they have generally been considered in relation to how they affect levels of violence. However, new research in the fields of anthropology, security, and development studies suggests that ceasefires can have many more ramifications. These range from their ability to influence governance institutions, property and citizenship rights, economic networks, and security mechanisms. Consequently, this article suggests that a broader legal framework is needed through which to consider ceasefires and their consequences. While canvassing the option of ceasefires being types of contractual documents or as special agreements under Common Article 3 of the Geneva Conventions, the article concludes that the best way to regulate ceasefire agreements is through an expanded version of lex pacificatoria . Rather than being governed by hard international law, such a move would allow for the implementation of more flexible programmatic standards to influence the myriad ways ceasefires are negotiated, the conduct of belligerents, and their diverse effects on the ground during wartime.